Nadzór bankowy w krajach strefy euro - zadania, struktura i kierunki ewolucji - Gostomski, Eugeniusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Internationalization of banking activity, growth of the role of capital market for banks, enlargement of the size of banks as a result of mergers and wider use of outsourcing make a big challenge for the system for banking supervision. Banks engaged in international trade are exposed on the risk of contagion effect by crisis in other countries. In the European Union there is a decentralized model of banking supervision, but the local supervisors co-operate intensively. In some Member States there is an integrated model of banking supervision, but in the majority of countries it functions on separate segments of financial market. At present in the European Union there are no possibilities to establish a supranational system of banking supervision. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 124-130